Enhancement of Productivity and Efficiency through a Service Model with Lean Service Tools-Case Study - Torres Millones, Carmen Alondra (2023)
This research aims to enhance productivity in the preparation and presentation of hamburgers at an artisanal category restaurant. The goal is to increase productivity and efficiency while reducing reprocessing rates during practice. This article introduces an innovative operational model that integrates Facility Layout Design (FLD), Standardized Work (STW), and autonomous maintenance under the Plan-Do-Check-Act (PDCA) cycle framework to address the suboptimal utilization of workstations and the current layout, as well as the high error rates in the preparation process and the lack of preventive maintenance for the machines involved in the operation. The model is divided into four phases. The first phase consists of diagnosing the initial situation of the company. The second phase encompasses the implementation of Lean Service and FLD tools. Subsequently, a 12-week implementation phase took place. Finally, the implemented improvements were assessed, and pre-and post-implementation indicators were compared. Statistical validation of the improved indicators was performed using Minitab Statistics V21 software. The results confirmed an 18% increase in productivity and a 27% increase in efficiency. Additionally, reprocessing was reduced by 50%. This article serves as a reference for better decision-making for managers and entrepreneurs within the artisanal food cluster seeking to enhance productivity and efficiency and reduce reprocessing rates in similar small and Medium-Sized Enterprises (MSE).